Severe Measles-Related Pneumonia in Children Treated with Steroid - Alanazi, Aeshah; Otayn, Bashaer; Al Fawaz, Tariq S. (Journal of Pediatric Infectious Diseases, 2020)
Measles still remains one of the major causes of childhood morbidity and mortality in developing countries. It is a highly contagious viral illness with worldwide occurrence. In spite of a highly vaccinated population, a measles outbreak still occurred in Saudi Arabia in 2019, mainly in the northern regions. Measles-related pneumonia (MRP) is the commonest cause of death in children with measles. In this study, we described two cases of severe MRP in children, who were successfully treated with steroid during the 2019 outbreak.
Keywords: measles; pneumonia; prednisolone; children